Ambientes de aprendizaje y su incidencia en la comprensión lectora en los estudiantes de la UE Emigdio Esparza Moreno, Babahoyo. 2022 - España Santillán, Jhoselín Adriana (2022)
Learning demands an adequate environment and has many components that are considered effective and efficient. While reading comprehension is the ability to decode text with accuracy and automation, maintaining the correct use of sentences and appropriate expressions to convey meaning. Through the pre-professional practices carried out in the 4th year of EGB in the Educational Unit "Emigdio Esparza Moreno", it was observed that the students of this course present problems when carrying out reading practices. Therefore, in the search for solutions in the development of reading fluency, it is intended to determine the possible relationship that the learning environment presents in the reading fluency of students. The present work is justified theoretically because it will allow the investigation and fit many points in relation to the variables. In the same way, it will justify in practice, since the knowledge acquired can be applied. Finally, it will justify socially, since the project will be a contribution to improve the problematic reality detected in the Emigdio Esparza Moreno Educational Unit.